Scent‐Mark Identification and Scent‐Marking Behaviour in African Wild Dogs (Lycaon pictus). (21st June 2013) - Jordan, Neil R.; Golabek, Krystyna A.; Apps, Peter J.; Gilfillan, Geoffrey D.; McNutt, John W.; Janik, V.
Abstract Scent‐marking is common in mammals, but where signals are carried by urine and faeces, distinguishing between scent‐marking and mere elimination is problematic. To do so, we documented behaviours and context variables associated with urination and defecation in free‐ranging endangered African wild dogs (Lycaon pictus) and tested whether these were related to the responses of other dogs to deposits. We found that distinct postures were almost uniquely associated with deposits by dominant wild dogs, were more common during urination than defecation, and increased the likelihood that these deposits would be investigated by other wild dogs. The likelihood of investigation depended on the sex and dominance status of the depositor, the type of deposit and the substrate. Urine from dominant females was more likely to be investigated by other wild dogs than any other deposits, and deposits placed on vegetation were more likely to be investigated than those on bare ground. The likelihood that a deposit would be overmarked was affected by the deposit type and the sex and dominance status of the last depositor. Collectively, these results suggest that dominant wild dog urine is of greatest interest to other dogs. Our results show that some deposits by African wild dogs are not scent‐marks and that detailed observations of behaviours and context variables during elimination events can be used to distinguish deposits that are likely to be of communication value.